Development of Iron and Zinc Biofortified Rice Variety for Nutrition Improvement in Bangladesh - Md. Ariful Islam; Md. Moniruzzaman Hasan; Tanbin Akter; Shahed Md. Saiful Islam (Food Science and Engineering, 2024)
Depleting micronutrients such as iron and zinc poses a serious risk to a population’s health in regions where nutrient-rich meals are unavailable, such as Bangladesh. We can engross the essential minerals using biofortified rice varieties enriched with essential minerals. We experimented to develop and evaluate a new high-yielding rice variety, Advanced Chemical Industries (ACI) dhan1, specifically for the rainy season in Bangladesh. We used high-yielding rice parent lines with high iron and zinc in the hybridization process, then grew and selected the resulting breeding lines during the rainy season of Bangladesh to identify the most suitable rice lines for the rainy season. The plant height and days to maturity traits were the same as shown in both cultivars, ACI dhan1 and Bangladesh Rice Research Institute (BRRI) dhan62 (standard check), which are 104 cm and 103 days, respectively. On the other hand, ACI dhan1 produced 6.05 tons per hectare, and BRRI dhan62 yielded 4.33 tons per hectare. A quality analysis of the grain quantified that ACI dhan1 contained 8.21% protein and 25.12% apparent amylose. Similarly, ACI dhan1 had very high levels of Zn (24.8 ppm) and Fe (9 ppm). We observed a more than 70% improvement in milling capabilities and head rice recovery. In proposed variety trials, the Seed Certification Agency of Bangladesh identified an average yield advantage of more than 10% for ACI dhan1 in 10 locations. National Seed Board, Bangladesh, released it as a candidate for high-iron and zinc-enriched rice variety and approved its extensive cultivation in Bangladesh. Due to its high micronutrient content, excellent agronomic performance, and non-sticky cooking quality, ACI dhan1 presents itself as a variety of choice in Bangladesh’s pursuit of food and nutrition security. Thus, the present study demonstrates the large achievement of biofortification by ACI dhan1 and hence promises to be a strong weapon in the battle against malnutrition.